Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst